Diseño y simulación de una trilladora de quinua de hasta 350 kg/h para el proceso de pos cosecha del sector agrícola - Llumipanta Toro, Cesar Paúl (2016)
The purpose of this project is to design and simulate a quinoa threser, for the process of post-harvest agricultural sector. At first the study of the state of threser quinoa that allows to know this type of equipment manufactured. By analysis of its characteristics and elements of trite. It is proposed design alternatives, which it is determined as the best option thresher quinoa tubular type comprising a threshing cylinder and concave grain separation plant, a cleaning system through a sieve with longitudinal movement, the corresponding calculation of each thresher elements quinoa in effect the choice of standardized elements is performed. Through simulation in Autodesk Inventor static and dynamic analysis is performed and dynamically stress. The finite element method was used to simulate elements where Von Misses is obtained. Displacement and safety factor information it is performed a comparison with theoretically calculated and simulated data. The cost benefit study carried out for the future implementation of the thresher Quinoa is of great importance by letting know whether the proposed project is viable for implementation giving favorable results.